Buying insurance at low economic cost - the effects of bank capital buffer increases since the pandemic - Markus Behn; Marco Forletta; Alessio Reghezza (European Central Bank (ECB), 2024)
Using granular data from the European corporate credit register, we examine how increases in macroprudential capital buffer requirements since the pandemic have affected bank lending behaviour in the euro area. Our findings reveal that, for the average bank, the buffer requirement increases did not have a statistically significant impact on lending to non-financial corporations. Furthermore, while we document relatively slower loan growth for banks with less capital headroom, also these banks did not decrease lending in absolute terms in response to higher requirements. These findings are robust in various specifications and emerge for both loan growth at the bank-firm level and the propensity to establish new bank-firm relationships. At the firm level, we document some heterogeneity depending on firm type and firm size. Firms with a single bank relationship and small and micro enterprises experienced a relative reduction in lending following buffer increases, although substitution effects mitigated real effects at the firm level. Overall, the results suggest that the pronounced macroprudential tightening since late 2021 did not exert substantial negative effects on credit supply. Hence, activating releasable capital buffers at an early stage of the cycle appears to be a robust policy strategy, since the costs of doing so are expected to be low.
Keywords: E5; E51; G18; G21; 330; credit supply; bank lending; macroprudential policy; capital buffers